Analisis Diskursus Gender pada Salah Satu Bahan Ajar PAI - Mufidah, Zulfatul; Sifrotul Maftuhah (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
This study aims to examine gender representation in Islamic Religious Education textbooks, especially the Grade VI Akidah Akhlak Book of the Merdeka Curriculum. By using the Critical Discourse Analysis (AWK) approach of the Norman Fairclough model, researchers seek to identify and analyze gender biases and stereotypes hidden in the narrative, illustrations, and language structure of the textbook. The results showed that although narratively this book tends to use neutral language, from the visual aspect and the choice of characters, the dominance of men as the main actors is very visible. Women tend to be placed as extras or complements in various social, environmental, and moral activities. These findings indicate an implicit bias that has the potential to strengthen gender stereotypes in the educational environment. This study recommends the need to revise textbooks to be more inclusive and gender-perspective, in order to support fair and equal religious education. Keyword: Gender Representation, Akidah Akhlak Book, Critical Discourse Analysis